EUDAIMONIA DALAM FILSAFAT STOA SEBAGAI DASAR ETIKA - Maulyana, Andi; Indah, Astrid Veranita (Aqidah-Ta: Jurnal Ilmu Aqidah, 2023)
The term eudaimonia or happiness first appeared in Aristotle's Nicomachean Ethics in book I. Aristotle considered happiness to be something that could be achieved in ordinary activities, not something that was independent of that activity. Happiness makes human life better based on moral values. Happiness is related to birth, life processes, and events after death. Discussion of happiness in later times continued into the time of Stoic philosophy. The meaning of happiness which was interpreted inclusively during Aristotle's time shifted into a pragmatic meaning, about how an individual is able to control negative emotions in social life. The teachings brought by the Stoics taught that when a human being has an awareness of the virtues he has, then he will consider all things before deciding what action to take so he avoids negative emotions.